Does sagittal position of the CTDR-related centre of rotation influence functional outcome? Prospective 2-year follow-up analysis - Suchomel, P; Jurák, L; Antinheimo, J; Pohjola, J; Stulik, J; Meisel, H-J; Čabraja, M; Woiciechowsky, C; Bruchmann, B; Shackleford, I; Arregui, R; Sola, S (European spine journal, 2014)
PURPOSE: Recent studies describe significant rates of heterotopic ossification (HO) after cervical total disc replacement (CTDR). Little is known about the reasons, and one aspect that requires further in vivo investigation is the biomechanical alteration after CTDR and the role of the implant-related centre of rotation (CORi) in particular. The role of the sagittal position of the CORi on functional outcome in two versions of a semi-constrained disc prosthesis with sagittally different CORi is the topic of this study. METHODS: Patients were candidates for single-level CTDR between C3 and C7 who suffered from CDDD and received a standard or flat version of activ C™ (Aesculap AG, Tuttlingen). Clinical and radiographic assessments were determined preoperatively, intraoperatively, at discharge and again at 6 weeks, 6 months, 1 and 2 years. Radiographic examinations were performed independently using specialized quantitative motion analysis software. RESULTS: Clinical outcome improved significantly regarding NDI as well as VAS on neck and arm pain with no differences in mean improvement by study group. Segmental angle measures show a significantly better lordotic alignment for both groups after surgery, but the degree of correction achieved is higher in the flat group. Correlation analysis proves that the more anterior the CORi is positioned, the higher the lordotic correction is achieved (Pearson rho -0.385). Segmental ROM decreased in the standard group but was maintained for flat implants. At present, our data do not demonstrate a correlation between CORi and ROM at 2 years. Two years after surgery, severe HO grade III-IV was present in 31.6 % standard and 13.1 % flat cases with significant differences. Grouping according to HO severity showed comparable sagittal positions of CORi for flat implants but a more posterior position in the severe HO group for standard implants. CONCLUSIONS: Our results confirm the influence of CORi location on segmental alignment, kinematics and HO for a semi-constrained CTDR, but it also indicates a multifactorial process.
Keywords: Total Disc Replacement; Male; heterotopická osifikace; Lordosis; následné studie; Ossification, Heterotopic; Adult; Prospective Studies; dospělí; mužské pohlaví; Intervertebral Disc; lordóza; Severity of Illness Index; artroplastika meziobratlové ploténky; Cervical Vertebrae; Follow-Up Studies; lidé; ženské pohlaví; Humans; krční obratle; meziobratlová ploténka; stupeň závažnosti nemoci; Female; lidé středního věku; Middle Aged; prospektivní studie